Thermoregulation and Respiratory Metabolism in two Brazilian Stingless Bee Subspecies of Different Climatic Distribution, Tetragonisca angustula fiebrigi and T a angustula (Hymenoptera: Apidae: Meliponinae) - Proni, Edson A.; Hebling, Maria José A. [UNESP] (Schweizerbart, 1996)
The thermoregulatory capacity of colonies of the stingless bee subspecies Tetragonisca angustula fiebrigi Schwarz 1938, and Tetragonisca angustula angustula Latreille 1807, was investigated during winter and summer. The temperatures [T] inside and outside the nests were measured for 48 hh every 2 hh. In the brood area, the mean T observed for T a fiebrigi are 28.1° and 29.5° C, respectively, during winter and summer, whereas for T a angustula they are 28.6° and 31.6° C The ambient T in the same period range from 10.5° - 24.4° C (winter) and 20.1 - 36.3° C (summer). In workers, the respiratory rates [RR] increase with a rise in T, however, the differences between workers of the subspecies are not significant in contrast to the RR measured within subspecies in winter and summer. The Q10 values indicate an optimal T range from 15 - 25° C in winter, and from 20 - 30° C in summer for T a fiebrigi. For T a angustula the corresponding values were 25 - 35° C and 30 - 40° C, respectively.
Keywords: Brood area; Respiratory rate; T a angustula Latreille 1807; Temperature range; Tetragonisca angustula fiebrigi schwarz 1938; Thermoregulatory capacity